Jawabanmu

2014-09-05T22:50:59+07:00
A = ²log3
b = ³log5

1. ²log5 = ³log5 / ³log2
            = b / 1/a
            = b × a/1
            = ab
2. ⁶log75 = ²log75 / ²log6
              = ²log(3×25) / ²log(3×2)
              = ²log3 + ²log25 / ²log3 + ²log2
              = a + ²log5² / a + 1
              = a + 5²log2 / a + 1
              = a + 5 + 1 / a + 1
              = a + 6 / a + 1
3. ⁹log120 = ³log120 / ³log9
                = ³log(5×24) / ³log3³
                = ³log5 + ³log24 / 1 × 3
                = b + ³log(2×12) / 3
                = b + ³log2 + ³log24 / 3
                = b + 1/a + ³log(2×12)  / 3
                = b + 1/a + ³log2 + ³log12 / 3
                = b + 1/a + 1/a + ³log(2×6) / 3
                = b + 1/a + 1/a + ³log2 + ³log6 / 3
                = b + 1/a + 1/a + 1/a + ³log(2×3) / 3
                = b + 1/a + 1/a + 1/a + ³log2 + ³log3 / 3
                = b + 1/a + 1/a + 1/a + 1/a + 1 / 3
                = b + 1+1+1/a + 1 / 3
                = b 3/a + 1 / 3
                = b 3/a / 3